2015
DOI: 10.1016/j.bbamcr.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Fast endocytic recycling determines TRPC1–STIM1 clustering in ER–PM junctions and plasma membrane function of the channel

Abstract: Stromal interaction molecule 1 (STIM1) senses depletion of ER-Ca2+ store and clusters in ER-PM junctions where it associates with and gates Ca2+ influx channels, Orai1 and TRPC1. Clustering of TRPC1 with STIM1 and Orai1 in these junctions is critical since Orai1-mediated Ca2+ entry triggers surface expression of TRPC1 while STIM1 gates the channel. Thus, plasma membrane function of TRPC1 depends on the delivery of the channel to the sites where STIM1 puncta are formed. This study examines intracellular traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Importantly, co-expression of Rab4 with Rab5, but not STIM1 or Rab11, rescued routing of TRPC1 to the plasma membrane (recovery of TRPC1 function shown in Figure 1C). Notably, while STIM1 is required for recruitment of TRPC1 into the plasma membrane and activation after cell stimulation, it is not involved in intracellular trafficking of the channel [75]. This study also showed that internalization of TRPC1 occurs via an endocytic pathway mediated by ARF6 that is independent of clathrin and Cav-1.…”
Section: Modulation Of Trpc1 Expression and Activity At The Plasma Mementioning
confidence: 64%
See 3 more Smart Citations
“…Importantly, co-expression of Rab4 with Rab5, but not STIM1 or Rab11, rescued routing of TRPC1 to the plasma membrane (recovery of TRPC1 function shown in Figure 1C). Notably, while STIM1 is required for recruitment of TRPC1 into the plasma membrane and activation after cell stimulation, it is not involved in intracellular trafficking of the channel [75]. This study also showed that internalization of TRPC1 occurs via an endocytic pathway mediated by ARF6 that is independent of clathrin and Cav-1.…”
Section: Modulation Of Trpc1 Expression and Activity At The Plasma Mementioning
confidence: 64%
“…Internalization of TRPC1 from the plasma membrane, and its transport to this region, is determined by endocytic and exocytic vesicular trafficking pathways, respectively. A recent study has identified the essential vesicular compartments and Rab proteins involved in regulating intracellular trafficking of TRPC1 [75]. This study demonstrated that TRPC1 is trafficked via a fast endocytic recycling pathway which involves Rab5 and Rab4 (Figure 2A–C).…”
Section: Modulation Of Trpc1 Expression and Activity At The Plasma Mementioning
confidence: 74%
See 2 more Smart Citations
“…; de Souza et al. ). Calcium influx through Orai and direct interactions between STIM and TRPC1 regulates the delivery of TRPC1 channels to specific domains within the plasma membrane (Ong et al.…”
Section: Discussionmentioning
confidence: 97%